Quantification of volatile organic compounds in smoke from prescribed burning and comparison with occupational exposure limits - E. Romagnoli; T. Barboni; P.-A. Santoni; N. Chiaramonti (Natural Hazards and Earth System Sciences, 2014)
Prescribed burning represents a serious threat to personnel fighting fires due to smoke inhalation. The aim of this study was to investigate exposure by foresters to smoke from prescribed burning, focusing on exposure to volatile organic compounds (VOCs). The methodology for smoke sampling was first evaluated. Potentially dangerous compounds were identified among the VOCs emitted by smoke fires at four prescribed burning plots located around Corsica. The measured mass concentrations for several toxic VOCs were generally higher than those measured in previous studies due to the experimental framework (short sampling distance between the foresters and the flame, low combustion, wet vegetation). In particular, benzene, phenol and furfural exceeded the legal short-term exposure limits published in Europe and/or the United States. Other VOCs such as toluene, ethybenzene or styrene remained below the exposure limits. In conclusion, clear and necessary recommendations were made for protection of personnel involved in fighting fires.